TREC-IN: gene knock-in genetic tool for genomes cloned in yeast - Chandran, S.; Noskov, V.N.; Segall-Shapiro, T.H.; Ma, L.; Whiteis, C.; Lartigue, C.; Jores, Joerg; Vashee, S.; Ray-Yuan Chuang (Springer, 2014)
With the development of several new technologies using synthetic biology, it is possible to engineer genetically intractable organisms including Mycoplasma mycoides subspecies capri (Mmc), by cloning the intact bacterial genome in yeast, using the host yeast’s genetic tools to modify the cloned genome, and subsequently transplanting the modified genome into a recipient cell to obtain mutant cells encoded by the modified genome. The recently described tandem repeat coupled with endonuclease cleavage (TREC) method has been successfully used to generate seamless deletions and point mutations in the mycoplasma genome using the yeast DNA repair machinery. But, attempts to knock-in genes in some cases have encountered a high background of transformation due to maintenance of unwanted circularization of the transforming DNA, which contains possible autonomously replicating sequence (ARS) activity. To overcome this issue, we incorporated a split marker system into the TREC method, enabling seamless gene knock-in with high efficiency. The modified method is called TREC-assisted gene knock-in (TREC-IN). Since a gene to be knocked-in is delivered by a truncated non-functional marker, the background caused by an incomplete integration is essentially eliminated. In this paper, we demonstrate applications of the TREC-IN method in gene complementation and genome minimization studies in Mmc. In the first example, the Mmc dnaA gene was seamlessly replaced by an orthologous gene, which shares a high degree of identity at the nucleotide level with the original Mmc gene, with high efficiency and low background. In the minimization example, we replaced an essential gene back into the genome that was present in the middle of a cluster of non-essential genes, while deleting the non-essential gene cluster, again with low backgrounds of transformation and high efficiency. Conclusion Although we have demonstrated the feasibility of TREC-IN in gene complementation and genome minimization studies in Mmc, the applicability of TREC-IN ranges widely. This method proves to be a valuable genetic tool that can be extended for genomic engineering in other genetically intractable organisms, where it may be implemented in elucidating specific metabolic pathways and in rationale vaccine design.